Application of evolutionary algorithms for the model-free determination of scattering matrix and the numerical diagonalization of Nilsson-model Hamiltonian - Vodin, A.N.; Korda, V.Yu.; Dovbnya, A.N.; Molev, A.S.; Korda, L.P. (Вопросы атомной науки и техники, 2004)
A new model-free approach for analyzing the intermediate-energy light nucleus-nucleus elastic-scattering differential cross-sections is proposed to extract the numerical dependencies of S-matrix modulus and nuclear phase on
angular momentum directly from the experimental data via the evolutionary algorithm. The refractive and absorptive properties of the ¹⁶О – ¹⁶О-interaction at Е = 22…44 МeV/nucleon are studied. The new approach based on a
genetic algorithm is presented to diagonalize the Hamiltonian matrix of the Nilsson-model for the deformed axially
symmetric nucleus. The tests witness that the larger the matrix size the more effective the genetic approach becomes
comparing to the traditional diagonalization methods. Запропоновано новий безмодельний підхід для аналізу диференціальних перерізів пружного розсіяння
легких ядер проміжних енергій ядрами, що дає змогу визначати числові залежності модуля і ядерної фази
матриці розсіяння від орбітального моменту безпосередньо з експериментальних даних за допомогою
еволюційного алгоритму. Досліджені заломлюючі та поглинаючі властивості ¹⁶О – ¹⁶О-взаємодії при
Е = 22…44 МеВ/нуклон. Представлено новий метод діагоналізації матриці гамільтоніану в моделі Нільсона
деформованого ядра з аксіальною симетрією, що застосовує генетичний алгоритм. Тестування довело, що
чим більше розмір діагоналізуємої матриці, тим ефективнішим виявляється генетичний підхід порівняно з
традиційними методами діагоналізації.
Предложен новый безмодельный под Предложен новый безмодельный подход для анализа дифференциальных сечений упругого рассеяния
легких ядер промежуточных энергий ядрами, позволяющий извлекать численные зависимости модуля и
ядерной фазы матрицы рассеяния от орбитального момента непосредственно из экспериментальных данных
с помощью эволюционного алгоритма. Изучены преломляющие и поглощающие свойства ¹⁶О – ¹⁶О-взаимодействия при Е = 22…44 МэВ/нуклон. Представлен новый метод диагонализации матрицы гамильтониана в
модели Нильссона деформированного ядра с аксиальной симметрией, использующий генетический алгоритм. Тестирование показало, что чем больше размер диагонализуемой матрицы, тем эффективнее оказывается генетический подход по сравнению с традиционными методами диагонализации.